The holy river of God : currents and contributions of the Wesleyan Holiness stream of Christianity - Callen, Barry L. (California : Aldersgate Press, 2016)
Today's Christian leaders have come to new heights of frustration seeking ways to revitalize their congregations and denominations. Welcome answers are now coming from an ancient Christian tradition is biblically rooted, informed by Wesleyan theology, and proving timely in the twenty-first century. The Wesleyan Holiness stream of the church is rich with history, serious theological thiking, and powerful social manifestations of God's transforming work. It has taken various forms, including numerous denominational families, thirteen of which are detailed here by their own leading exponents. These faith families have networked to form the Weselyan Holiness Connection. Joining the denominational histories are the stories of regional networks of pastors, leaders in Christian higher education, Aldersgate Press, and several associated ministries in North America and far beyond that together have produced position statements on several of the most pressing social issues of our time. These include the "Holiness Manifesto," "A Call to Full Participation" (women in the Wesleyan Holiness tradition), "Gracefully Engaging the LGBT Conversation," and a "Declaration of Freedom" (human trafficking). Found here are the currents and contributions of Christian holiness in the broad Wesleyan tradition, past and present, found inside and outside the established churches. It is a significant part of the rushing river originating in God's heart and now being energized by the Wesleyan Holiness Connection on behalf of the life and mission of today's churches. To God be the glory!
Section I: Holy river and its streams -- Our guiding vision forward / Kevin W. Mannoia -- Holiness stream in biblical and historical context / Barry L. Callen and Kenneth L. Waters, Sr. -- John Wesley's holiness themes / Don Thorsen and Kristen Oh -- International holiness and Pentecostal movements / David Bundy -- American holiness movement / Stan Ingersol -- Section II: Currents within the Wesleyan holiness stream -- Assemblies of God / Darrin J. Roders -- Brethren in Christ / E. Morris Sider -- Christian & Missionary Alliance / Bernie A. Van De Walle -- Church of God (Anderson, In) / Barry L. Callen -- Church of God (Cleveland, Tn) / David G. Roebuck -- Church of the Nazarene / Steven Hoskins -- Free Methodist Church / Howard A. Snyder -- Grace Communion International / Joseph Tkach -- International Pentecostal Holiness Church / A.D. Beacham, Jr. -- International Church of the Foresquare Gospel / Jack W. Hayford -- Salvation Army / Jonathan S. Raymond -- United Methodist Church / Laurence W. Wood -- Wesleyan Church / Robert Black and Jo Anne Lyon -- Section III: Story of the Wesleyan Holiness Connection -- Wesleyan Holiness Connection / Christopher D. O'Brien -- Aldersgate Press / Barry L. Callen, editor -- WHC networks -- Regional networks: United States / Carla and Charles Sunberg -- Wesleyan Holiness Connection, Brazil and globally / Ildo Mello and Clovis Paradela -- WHC President's Network / James L. Edwards -- WHC Associated Ministries -- America's Christian Credit Union / Mendell L. Thompson and Fawn Imboden -- Junia project / Kate Wallace Nunneley -- Wesleyan holiness women clergy / MaryAnn Hawkins -- World Gospel Mission / Hubert P. Harriman and Dan Schafer -- Wesleyan Theological Society / Barry L. Callen and Diane Leclerc -- Freedom Network / Kate Wallace Nunneley -- Section IV: WHC resource documents on today's critical issues -- Holiness Manifesto: Wesleyan Holiness Connection, February 2006 -- Fresh eyes of holiness: Wesleyan Holiness Connection, March 2007 -- Call to full participation: women in the Wesleyan Holiness tradition -- Gracefully engaging the LGBT conversation: Wesleyan Holiness Connection, September 2015 -- Human trafficking: declaration for freedom, December, 2013.
Includes bibliographical references.
Keywords: Assemblies of God -- History; Brethren in Christ Church -- History; Christian and Missionary Alliance -- History; Church of God (Anderson, Ind.) -- History; Church of God (Cleveland, Tenn.) -- History; Church of the Nazarene -- History; Free Methodist Church of North America -- History; Grace Communion International -- History; International Pentecostal Holiness Church -- History; International Church of the Foursquare Gospel -- History; Salvation Army -- History; United Methodist Church (U.S.) -- History; Wesleyan Church -- History; Assemblies of God; Brethren in Christ Church; Christian and Missionary Alliance; Church of God (Anderson, Ind.); Church of God (Cleveland, Tenn.); Church of the Nazarene; Free Methodist Church of North America; International Church of the Foursquare Gospel; International Pentecostal Holiness Church; Salvation Army; United Methodist Church (U.S.); Wesleyan Church; Holiness churches -- History; Holiness churches; History